Preparation method and application of flexible nano material for photodynamic-immunotherapy
Through flexible nanomaterials prepared in photodynamic-immunotherapy, the enzyme-linked amplification reaction is used to generate oxygen in tumor cells and reduce lactic acid concentration, the efficacy of photodynamic-immunotherapy in hypoxia and high lactate microenvironment is solved. The problem limits significantly improves the therapeutic effect and reduces side effects.
Patent Information
- Application Number
- CN202411356017.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
Photodynamic-immunotherapy is limited in the hypoxia and high lactate microenvironment in tumors. The existing improvement methods have problems such as single effect, insufficient oxygen release, insufficient targeting and low stability.
Prepare a flexible nanomaterial, which uses enzyme-linked amplification reaction to generate oxygen in tumor cells and reduce lactic acid concentration, improve the microenvironment, and combine photosensitive to enhance therapeutic effect.
It significantly improves the oxygen generation efficiency and immune cell activity of photodynamic therapy, enhances the tumor-specific immune response, improves the efficacy of photodynamic-immunotherapy and reduces side effects.
Smart Images

Figure CN119215194A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a flexible nano material for photodynamic-immunotherapy, and also relates to the application of the flexible nano material prepared by the method in preparing anti-tumor drugs. Background Art
[0002] The treatment of malignant tumors still faces huge challenges worldwide. Although existing treatments (such as surgery, radiotherapy and chemotherapy) have made certain progress, the prognosis of patients is still not ideal. In recent years, immunotherapy, as an emerging treatment method, has shown significant potential. By mobilizing the patient's own immune system, immunotherapy can identify and attack tumor cells, thereby providing a more targeted and lasting anti-cancer effect. However, immunotherapy still faces many challenges in practical applications, such as immune escape, low response rate, and treatment-related toxic side effects. At the same time, photodynamic therapy has gradually become a promising tumor treatment method in recent years because it can directly kill tumor cells by generating reactive oxygen species through light-activated photosensitizers and causes less damage to surrounding normal tissues. Due to the complementary mechanisms of photodynamic therapy and immunotherapy, photodynamic-immunotherapy has gradually been regarded as a promising comprehensive tumor treatment strategy.
[0003] However, the actual effect of photodynamic-immunotherapy is largely limited by the hypoxic environment and high lactic acid microenvironment within the tumor. This complex microenvironment not only significantly weakens the efficiency of photodynamic therapy in producing reactive oxygen species, but also inhibits the activity of immune cells, thereby reducing the overall effect of the treatment. Many studies are currently trying to improve the hypoxic and high lactic acid microenvironment within the tumor through different strategies. However, these methods often have several key problems, including single action, insufficient oxygen release, low lactate clearance efficiency, insufficient targeting, and lack of stability, resulting in limited efficacy in practical applications. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing flexible nanomaterials for photodynamic-immunotherapy. The flexible nanomaterials prepared by this method can simultaneously improve the hypoxic and high lactic acid microenvironment in tumor cells, thereby effectively enhancing the efficacy of photodynamic-immunotherapy of tumors; another purpose of the present invention is to provide the application of the flexible nanomaterials prepared by the above method in the preparation of anti-tumor drugs.
[0005] Technical solution: The method for preparing the flexible nanomaterial for photodynamic-immunotherapy according to the present invention comprises the following steps:
[0006] (1) Mixing MSNs (mesoporous silica nanoparticles), polyethyleneimine and deionized water, shaking well and letting stand; centrifuging the mixture after standing, and then washing the solid matter after centrifugation to obtain MSNs-PEI particles;
[0007] (2) dispersing the MSNs-PEI particles in deionized water by ultrasonication, then adding glutaraldehyde thereto, and stirring thoroughly to obtain an aqueous solution of MSNs-PEI-GA;
[0008] (3) adding HSA (human serum albumin), activated CAT (catalase) and activated LOX (lactate oxidase) to the aqueous solution of MSNs-PEI-GA in step (2) in sequence, and mixing them thoroughly on a shaker to obtain nanoparticles (with a core-shell structure) coated with HSA, CAT and LOX on MSNs;
[0009] (4) adding the nanoparticles of step (3) into hydrofluoric acid, mixing thoroughly, and then rapidly centrifuging. The solid matter after centrifugation is washed with deionized water to obtain flexible HSA / CAT / LOX nanocapsules. After etching away the silica core, these nanocapsules form a hollow structure, retaining the encapsulating shell layer of HSA, CAT and LOX, so that they have better flexibility and biocompatibility.
[0010] (5) The flexible HSA / CAT / LOX nanocapsules were dispersed in deionized water, and the activated photosensitizer IR808 solution was added to the suspension of the flexible HSA / CAT / LOX nanocapsules, and the mixture was stirred on a shaker to ensure effective connection of the photosensitizer, thereby obtaining HSA / CAT / LOX nanocapsules connected with the photosensitizer.
[0011] Polyethyleneimine (PEI) uses its cationic properties to form a preliminary modification layer by surface electrostatic adsorption with negatively charged silica nanoparticles (MSNs); then, glutaraldehyde (GA) undergoes a condensation reaction with the amino group of PEI through its aldehyde group to further cross-link and modify the surface of the nanoparticles, thereby enhancing their stability and biocompatibility; in subsequent modifications, HSA, CAT, and LOX are connected to GA to form nanospheres with a core-shell structure through a condensation reaction between the amino group and the carboxyl group.
[0012] Wherein, in step (1), the mixing mass ratio of MSNs (mesoporous silica nanoparticles) and polyethyleneimine is 2:1.
[0013] In step (3), CAT is activated by the following method: specifically, CAT is dissolved in dimethyl sulfoxide (DMF), and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added thereto, and the mixture is thoroughly mixed on a shaker.
[0014] Wherein, in step (3), LOX is activated by the following method: specifically, LOX is dissolved in dimethyl sulfoxide, and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added thereto, and the mixture is fully mixed on a shaker.
[0015] Wherein, in step (3), the added mass ratio of HSA, CAT and LOX is 10:2:1.
[0016] Wherein, in step (3), the mass ratio of MSNs-PEI-GA to HSA added is 1:1.
[0017] Wherein, in step (4), the volume fraction of HF is 0.5% (v / v), which is the final concentration after 50-fold dilution.
[0018] In step (5), the photosensitizer IR808 is activated by the following method: dissolving the photosensitizer IR808 in dimethyl sulfoxide, then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide thereto, and mixing them thoroughly on a shaker in the dark to prevent the photosensitizer from degrading. EDC and NHS activate the carboxyl functional group of the photosensitizer IR808; the photosensitizer IR808 and HSA, CAT, and LOX are finally linked through an amide reaction.
[0019] Wherein, in step (5), the added mass ratio of activated photosensitizer IR808 to flexible HSA / CAT / LOX nanocapsules is 1: 10. Flexible HSA / CAT / LOX nanocapsules are flexible and have a large specific surface area, and can load more photosensitizer IR808.
[0020] Application of the flexible nanomaterial for photodynamic-immunotherapy prepared by the preparation method in the preparation of anti-tumor drugs.
[0021] Human serum albumin can bind to the GP60 receptor on the cell, promote the flexible nanoparticles of the present invention to pass through the endothelial cell barrier, and increase their accumulation at the tumor site. This process can not only improve the targeted delivery efficiency of drugs in tumors, but also prolong the circulation time of drugs and enhance the overall therapeutic effect. Utilize flexible nanomaterial structure: Flexible nanomaterials can provide higher cell uptake efficiency due to their unique physical properties (flexibility and low Young's modulus, making it easier to enter cells), thereby not only improving the enrichment and penetration of drugs at the tumor site, but also significantly improving the therapeutic effect while reducing side effects.
[0022] Aiming at the hypoxia and high lactate characteristics in the tumor cell microenvironment, the flexible nanomaterial prepared by the present invention can target and regulate the tumor microenvironment. The flexible nanomaterial encapsulates human serum albumin (HSA), catalase (CAT) and lactate oxidase (LOX) in a flexible carrier to achieve dual regulation of effectively alleviating the hypoxic state and reducing the lactate concentration in the tumor microenvironment. CAT significantly improves the hypoxic microenvironment in tumor cells by converting hydrogen peroxide into oxygen, while LOX generates additional hydrogen peroxide by oxidizing lactate, further enhancing the efficacy of CAT, forming an enzyme-linked amplification reaction, thereby activating the immune system, promoting macrophage M1 polarization, and maturation of dendritic cells, thereby significantly improving the effect of photodynamic-immunotherapy. The flexible nanomaterial of the present invention can achieve enzyme-linked amplification, significantly enhance the performance of CAT, and produce stable and sufficient oxygen, while photodynamic-immunotherapy relies on oxygen. Photodynamic immunotherapy improves the tumor immunosuppressive microenvironment by producing reactive oxygen and inducing immunogenic cell death, which can significantly enhance tumor-specific immune response.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the flexible nanomaterial prepared by the method of the present invention has efficient tumor targeting, stable morphology and good enzyme catalytic activity, and the flexible nanomaterial of the present invention can achieve enzyme-linked level amplification. The present invention can generate stable and sufficient oxygen in tumor cells through enzyme-linked level amplification, thereby effectively improving the hypoxic and high lactic acid microenvironment in tumor cells, thereby improving the efficiency of photodynamic therapy in generating reactive oxygen species and directly killing tumor cells through reactive oxygen species; on the other hand, it can increase the activity of immune cells, cooperate with photodynamic immunotherapy to induce immunogenic cell death to activate the immune system, promote macrophage M1 polarization, and dendritic cell maturation, so as to achieve the purpose of significantly improving the effect of photodynamic-immunotherapy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a flow chart of the preparation method of the present invention;
[0025] Figure 2 (a) is a TEM image of the flexible nanomaterial of Example 1, Figure 2 (b) is the hydrodynamic size of the flexible nanomaterial in Example 1, Figure 2 (c) is the zeta potential of the flexible nanomaterial in Example 1;
[0026] Figure 3 The enzyme catalytic activity of the flexible nanomaterial in Example 1;
[0027] Figure 4 The production of active oxygen by different nanomaterials under laser irradiation;
[0028] Figure 5To verify the targeting of the etched flexible nanomaterial (HSA / CAT / LOX@IR808) to tumor cells in Example 1;
[0029] Figure 6 To verify the effect of the flexible nanomaterials in Example 1 on the hypoxic and high lactic acid microenvironment in tumor cells;
[0030] Figure 7 To verify the anti-tumor effect of the flexible nanomaterial in Example 1;
[0031] Figure 8 To verify the immune activation effect of the flexible nanomaterial in Example 1. DETAILED DESCRIPTION
[0032] Example 1
[0033] like Figure 1 As shown, the method for preparing the flexible nanomaterial for photodynamic-immunotherapy of the present invention comprises the following steps:
[0034] (1) Synthesis of silica nanoparticles:
[0035] 0.32 g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in a mixed solution consisting of 60 mL of ethanol, 150 mL of deionized water, and 1 mL of concentrated ammonia (mass fraction 25 wt%), and stirred in a 35 °C water bath for 1 hour to ensure adequate mixing and stabilize the solution;
[0036] Add 1 mL of tetraethyl orthosilicate (TEOS) to the above solution, and continue stirring at 35°C and 500 rpm for 3 hours to promote the formation of silica nanoparticles;
[0037] In order to remove the surfactant CTAB, the obtained silica nanoparticles were dispersed in 400 mL of ethanol solution containing 800 μl of concentrated hydrochloric acid and stirred in a 60°C water bath. After stirring, the silica nanoparticles were separated. To ensure the complete removal of CTAB, this extraction process was repeated three times. Finally, the CTAB-free mesoporous silica nanoparticles (MSNs) were dispersed in 25 mL of deionized water for storage after washing twice with ethanol and then twice with deionized water.
[0038] (2) Synthesis of silica nanoparticles encapsulating HSA, CAT and LOX:
[0039] 10 mL of MSNs (4 mg / mL), 2 mL of polyethyleneimine (PEI, 10 mg / mL) and 8 mL of deionized water were mixed, shaken thoroughly and allowed to stand for 20 minutes; then, the mixture was centrifuged at 15000 rpm for 5 minutes and washed three times with deionized water; the obtained MSNs-PEI was ultrasonically dispersed in 15 mL of deionized water, 5 mL of glutaraldehyde (GA) was added thereto, and the mixture was stirred on a shaker at 200 rpm for 12 hours; after the reaction, the solid was separated and washed three times to obtain MSNs-PEI-GA;
[0040] 20 mg of MSNs-PEI-GA was dispersed in 15 mL of deionized water to obtain an aqueous solution of MSNs-PEI-GA, 5 mL of HSA (4 mg / mL, 20 mg in total), 4 mg of activated CAT and 2 mg of activated LOX were added to the aqueous solution of MSNs-PEI-GA in sequence, and mixed on a shaker for 12 hours; nanoparticles (with a core-shell structure) coated with HSA, CAT and LOX on MSNs were obtained;
[0041] CAT was activated by the following method: 10 mg CAT was dissolved in 10 mL dimethyl sulfoxide (DMF), and then 1 mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC, 10 mg / mL) and 1 mL N-hydroxysuccinimide (NHS, 10 mg / mL) were added thereto, and the mixture was mixed on a shaker for 8 hours; LOX was activated by the following method: 2 mg LOX was dissolved in 1 mL dimethyl sulfoxide, and then 2 mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide (1 mg / mL) and 2 mL N-hydroxysuccinimide (1 mg / mL) were added thereto, and the mixture was mixed on a shaker for 8 hours;
[0042] (3) Etching and forming flexible nanocapsules:
[0043] The nanoparticles obtained in step (2) were added to 5 mL of hydrofluoric acid (volume fraction 0.5% (v / v)), mixed thoroughly for 1 minute, and then rapidly centrifuged at 15000 rpm for 3 minutes; washed three times with deionized water, each time centrifuged at 15000 rpm for 5 minutes, and finally obtained flexible HSA / CAT / LOX nanocapsules;
[0044] (4) Connecting photosensitizer (IR808):
[0045] To activate the photosensitizer IR808, 2 mg of the photosensitizer IR808 was dissolved in 1 mL of dimethyl sulfoxide (DMF), and then 2 mL of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC, 1 mg / mL) and 2 mL of N-hydroxysuccinimide (NHS, 1 mg / mL) were added thereto, and mixed on a shaker in the dark for 8 h to prevent the photosensitizer from degrading;
[0046] 50 mg of flexible HSA / CAT / LOX nanocapsules were dispersed in 15 mL of deionized water, and 2 mL of activated photosensitizer IR808 solution (mass concentration of 2.5 mg / mL) was added to the suspension of flexible HSA / CAT / LOX nanocapsules and stirred on a shaker for 12 hours to ensure the effective connection of the photosensitizer to obtain nanocapsules HSA / CAT / LOX@IR808 connected with photosensitizer.
[0047] The HSA / CAT / LOX nanocapsules (flexible nanomaterials) synthesized in Example 1 and connected with photosensitizer were characterized by transmission electron microscopy (TEM) to determine their morphology. Figure 2 The TEM images showed that the etched flexible nanomaterial had a uniform hollow structure and slight wrinkles on the surface, indicating that it had good flexibility.
[0048] The hydrodynamic size and zeta potential of the sample were measured using a NanoBrook ZetaPALS instrument, and the hydrated diameter and Zeta potential of the nanoplatform were measured to evaluate its stability in aqueous solution. The results showed that the hydrated diameter of the flexible nanomaterial in Example 1 was about 310±20nm and the Zeta potential was -4mV, proving that it had good dispersibility and stability in aqueous solution.
[0049] Example 1 Enzyme catalytic activity of flexible nanomaterials:
[0050] The ELISA method was used to quantitatively evaluate the catalytic activity of CAT and LOX constructed with flexible nanomaterials. The flexible nanomaterials, standard substances, and HRP-labeled detection antibodies were sequentially added to a microplate pre-coated with target enzyme antibodies. After incubation, washing, and color development, the absorbance of the reaction solution was measured to calculate the enzyme activity.
[0051] Figure 3 (a) Elisa method was used to detect the CAT activity in pure CAT and etched HSA / CAT / LOX@IR808, and no significant difference was found between the two (p<0.05). Figure 3(b) Elisa method was used to detect the LOX activity in pure LOX and etched HSA / CAT / LOX@IR808, and no significant difference was found between the two (p<0.05).
[0052] pass Figure 3 The results showed that the CAT and LOX enzymes in the flexible nanomaterial of Example 1 maintained efficient catalytic activity, indicating that the flexible nanomaterial of Example 1 has good enzyme catalytic function.
[0053] The flexible nanomaterial of Example 1 can generate sufficient reactive oxygen species through enzyme-linked amplification. Under in vitro conditions, the reactive oxygen species (ROS) generated by different nanomaterials (HSA / CAT / LOX, HSA@IR808, HSA / CAT@IR808, HSA / CAT / LOX@IR808), either alone or with the addition of H2O2 (3wt%), under laser irradiation were detected by SOSG probe. The suspension of the flexible nanomaterial of Example 1 was mixed with the SOSG probe, and then the fluorescence intensity was measured at 0, 1, 3, 5, and 10 minutes under 808nm laser irradiation to evaluate the generation of ROS.
[0054] Figure 4 In order to use the SOSG method to determine the generation of active oxygen by different materials under 808nm laser irradiation, Figure 4 The data showed that the HSA / CAT / LOX@IR808 encapsulating CAT and LOX prepared in Example 1 was able to stably generate more ROS than HSA / CAT@IR808, indicating that the present invention can effectively amplify the generation of ROS in photodynamic therapy through enzyme-linked reaction, thereby improving the treatment effect. Therefore, the flexible nanomaterial in Example 1 can significantly increase the generation of ROS in the presence of H2O2.
[0055] Example 1 Flexible nanomaterials have good targeting effects:
[0056] The targeting property of the flexible nanomaterials in Example 1 was evaluated by cell uptake experiments. Under laser confocal microscopy, tumor cells took up the flexible nanomaterials at 1 hour, 3 hours, and 6 hours, respectively. Figure 5 The results show that the nanomaterials were successfully internalized by tumor cells in a time-dependent manner. After 1 hour, the nanoparticles began to gather around the cells, and after 3 and 6 hours, a large number of nanoparticles were visible in the cells. Especially after 6 hours, the intracellular uptake of the flexible nanomaterials reached the highest level, showing strong targeting and effective intracellular delivery capabilities. The flexible nanomaterials of the present invention always showed excellent internalization efficiency. This shows that the flexible nanomaterials have obvious advantages in targeted delivery and can enter the cells more effectively.
[0057] Example 1 Flexible nanomaterials can effectively improve the hypoxic and high lactic acid tumor microenvironment in tumor cells. Hypoxia-inducible factor 1α (HIF-1α) and lactic acid levels in tumor cells were measured to evaluate the effect of flexible nanomaterials on improving the tumor microenvironment. The level of HIF-1α in cells after nanomaterial treatment was determined by protein immunoblotting (WB). The lactic acid concentration in cells after nanomaterial treatment was determined by microplate assay.
[0058] Figure 6 (a) The WB experiment was used to detect the intracellular HIF-1α level. The measured results showed that the material containing CAT can reduce the intracellular HIF-1α level. The material containing both CAT and LOX in Example 1 can further reduce the intracellular HIF-1α level due to the enzyme-linked amplification effect. Figure 6 (b) Using a lactate detection kit, the lactate content in cells at different time points (6 hours, 12 hours, and 24 hours) was measured. The material containing both CAT and LOX in Example 1 was able to significantly alleviate the accumulation of lactate in tumor cells, and the effect was enhanced over time.
[0059] pass Figure 6 The results showed that the flexible nanomaterials in Example 1 can effectively reduce the levels of HIF-1α and lactic acid in cells, thereby significantly improving the hypoxic and high lactic acid microenvironment in tumor cells.
[0060] Example 1 Anti-tumor application of flexible nanomaterials: The cytotoxicity of the saline + laser group, IR808 + laser group, HSA@IR808 + laser group, HSA / CAT@IR808 + laser group and HSA / CAT / LOX@IR808 + laser group as well as the effects of IR808 illumination time and concentration were evaluated in tumor cells. Tumor cells were plated at 1×10 4 The cells were seeded at a density of 100 μg / cm2 in a 96-well plate and incubated overnight. Subsequently, the cells were treated with different nanomaterials and IR808 concentrations for 12 h. After treatment, the cells were illuminated with an 808 nm laser (1 W / cm 2 ) were irradiated for 0, 1, 3, and 5 minutes, respectively, and incubated for another 24 hours. The cytotoxicity of each group was quantified by adding 10 μL of CCK-8 solution to each well and measuring the absorbance at 450 nm after incubation at 37°C for 2 hours.
[0061] Figure 7(a) CCK-8 experiment, the results show that the cytotoxic effect of IR808 group, HSA@IR808 group, HSA / CAT@IR808 group and HSA / CAT / LOX@IR808 group increased significantly and gradually strengthened over time, which was significantly different from the control group (p<0.0001); this difference was more obvious when the NIR 808nm irradiation time was prolonged; Figure 7 (b) is a CCK-8 experiment, and the results show that higher concentrations of IR808 significantly enhanced PDT-induced cytotoxicity, with obvious differences among the concentration groups.
[0062] pass Figure 7 The results of the CCK-8 experiment showed that compared with the control group, the flexible nanomaterial in Example 1 significantly enhanced the anti-tumor effect of photodynamic therapy. With the increase of IR808 concentration and the extension of illumination time, the cell viability gradually decreased. Compared with other nanomaterials, the flexible nanomaterial in Example 1 showed stronger cytotoxicity when combined with photodynamic therapy, indicating that it has significant advantages in inhibiting tumor cell proliferation. This enhanced anti-tumor effect further verifies the potential application value of the flexible nanomaterial in Example 1 in photodynamic therapy.
[0063] Example 1 Powerful immune activation effect of flexible nanomaterials: The immune activation effect of the flexible nanomaterials of Example 1 on bone marrow-derived macrophages (BMDM) and dendritic cells (BMDC) was evaluated in in vitro experiments. First, primary cells were extracted from the bone marrow of mice, and induced to differentiate into BMDM by adding macrophage colony stimulating factor (M-CSF), and induced to differentiate into BMDC by adding interleukin-4 (IL-4) and granulocyte-macrophage colony stimulating factor (GM-CSF). Subsequently, the culture supernatant of tumor cells treated with simple saline + laser group, IR808 + laser group, HSA@IR808 + laser group, HSA / CAT@IR808 + laser group and HSA / CAT / LOX@IR808 + laser group was added to these BMDM and BMDC, and further incubated for 48 hours. Flow cytometry was used to analyze the M1 polarization of BMDM and the maturation of BMDC, and Elisa was used to detect the levels of cytokines such as TNF-α, IL-12, and IL-6 in different supernatants.
[0064] Figure 8 (a) Flow cytometry to evaluate the M1 polarization of BMDM. The results show that after PDT treatment with nanomaterials, the M1 polarization of macrophages can be significantly promoted due to the enzyme-linked amplification effect. The M1 polarization ratio in the HSA / CAT / LOX@IR808 group reached 43.5%; Figure 8(b) The levels of TNF-α and IL-6 in the supernatant after co-incubation of tumor cells and BMDM were measured by enzyme-linked immunosorbent assay. The levels of TNF-α and IL-6 increased significantly after nanomaterial treatment. Figure 8 (c) Flow cytometry for evaluating BMDCs. The results showed that after PDT treatment with nanomaterials, due to the presence of enzyme-linked amplification, BMDC maturation was significantly promoted, and the proportion of BMDC maturity in the HSA / CAT / LOX@IR808 group reached 67.0%; Figure 8 (d) The levels of TNF-α and IL-12 in the supernatant after co-incubation of tumor cells and BMDCs were determined by enzyme-linked immunosorbent assay. The levels of TNF-α and IL-12 increased significantly after nanomaterial treatment.
[0065] pass Figure 8 The results showed that the tumor cell culture supernatant treated with the flexible nanomaterials of Example 1 can significantly enhance the M1 polarization of BMDM and the maturity of BMDC. That is, the BMDM of the flexible nanomaterials treated group of Example 1 showed a higher proportion of M1 macrophages, and the expression of BMDC maturity markers also increased significantly. In addition, the levels of TNF-α, IL-12 and IL-6 in the flexible nanomaterials treated group of Example 1 were significantly increased, indicating that the flexible nanomaterials of the present invention can effectively promote the activation and functional enhancement of immune cells in vitro, thereby enhancing the anti-tumor immune response ability.
Claims
1. A method for preparing a flexible nanomaterial for photodynamic-immunotherapy, characterized in that: The steps include: (1) Mixing MSNs, polyethyleneimine and deionized water, shaking thoroughly and letting stand; centrifuging the mixture after standing, and then washing the solid matter after centrifugation to obtain MSNs-PEI particles; (2) dispersing the MSNs-PEI particles in deionized water by ultrasonication, then adding glutaraldehyde thereto, and stirring thoroughly to obtain an aqueous solution of MSNs-PEI-GA; (3) adding HSA, activated CAT and activated LOX to the aqueous solution of MSNs-PEI-GA in step (2) in sequence, and mixing them thoroughly on a shaker to obtain nanoparticles with HSA, CAT and LOX coated on MSNs; (4) adding the nanoparticles of step (3) into hydrofluoric acid, mixing thoroughly, and then rapidly centrifuging, washing the solids after centrifugation with deionized water, and obtaining flexible HSA / CAT / LOX nanocapsules after washing; (5) The flexible HSA / CAT / LOX nanocapsules were dispersed in deionized water, and the activated photosensitizer IR808 solution was added to the suspension of the flexible HSA / CAT / LOX nanocapsules, and the mixture was fully stirred on a shaker to obtain HSA / CAT / LOX nanocapsules connected with the photosensitizer.
2. The preparation method according to claim 1, characterized in that: In step (1), the mixing mass ratio of MSNs to polyethyleneimine is 2:1 to 1.
5.
3. The preparation method according to claim 1, characterized in that: In step (3), CAT is activated by the following method: specifically, CAT is dissolved in dimethyl sulfoxide, and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added thereto, and the mixture is fully mixed on a shaker.
4. The preparation method according to claim 1, characterized in that: In step (3), LOX is activated by the following method: specifically, LOX is dissolved in dimethyl sulfoxide, and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added thereto, and the mixture is fully mixed on a shaker.
5. The preparation method according to claim 1, characterized in that: In step (3), the added mass ratio of HSA, CAT and LOX is 10:2:1-1.
2.
6. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of MSNs-PEI-GA to HSA is 1:1 to 1.
2.
7. The preparation method according to claim 1, characterized in that: In step (4), the volume fraction of HF is 0.5-0.6%.
8. The preparation method according to claim 1, characterized in that: In step (5), the photosensitizer IR808 is activated by the following method: specifically, the photosensitizer IR808 is dissolved in dimethyl sulfoxide, and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added thereto, and the mixture is thoroughly mixed on a shaker in the dark to prevent degradation of the photosensitizer.
9. The preparation method according to claim 1, characterized in that: In step (5), the added mass ratio of activated photosensitizer IR808 to flexible HSA / CAT / LOX nanocapsules is 1:10-12.
10. Use of the flexible nanomaterial for photodynamic-immunotherapy prepared by the preparation method of claim 1 in the preparation of anti-tumor drugs.
